Agile coaching journeys and daily practices - Adkins, Lyssa (Pearson, 2023)
An immersive audio series by Lyssa Adkins delving into the diverse, inspiring stories of agile coaches and sharing daily practices for improving coaching mindsets. Series Description In this two-part, ten-episode series, Lyssa Adkins shares five unique agile coaching journeys and guides listeners through five daily practices to get in the right coaching mindset. Within these narratives, listeners will discover instructional or inspirational elements--something that makes agile coaching "click" for them. Whether recognizing themselves in another's journey or realizing the uniqueness of their own experience, these stories encourage listeners to share their agile coaching journeys and invites them to explore the power of mindful practice. Related Learning: Book: Coaching Agile Teams: A Companion for ScrumMasters, Agile Coaches, and Project Managers in Transition Video: Coaching Agile Teams Part I: Agile Coaching Journeys Episode 1: Rachel Davies' Agile Coaching Journey In this episode, Lyssa takes the listeners through the agile coaching journey of Rachel Davies, an experienced facilitator and presenter at industry conferences worldwide. She shares in Rachel's own words her comprehensive journey, including struggles faced as an agile coach and the agile strategies that proved effective for her. The episode explores the approaches and techniques she embraced to promote agility and achieve progress. Episode 2: Daniel Mezick's Agile Coaching Journey In this episode, Lyssa dives into the agile coaching journey of Daniel Mezick, a seasoned technical trainer and agile coach. She explores Dan's entrepreneurial spirit within the agile context and delves into the valuable insights he's gained from group relations. She reflects, in Dan's own words, on the intriguing question of why Scrum works so well, offering unique perspectives and experiences from his agile endeavours. Episode 3: Lyssa Adkins' Agile Coaching Journey This episode encapsulates Lyssa's transformative journey from a project manager to a triumphant agile leader. Lyssa reflects on the shift in her perspective and shares insights gained from allowing the team to take charge of their agenda and fostering a collaborative working environment. The narrative delves into the profound depths of agile, introducing new ways of thinking that breathe life into agile methodologies. Lyssa emphasizes the crucial role of an agile coach--to empower the team to recognize their own capabilities. Episode 4: Martin Kearns' Agile Coaching Journey In this episode, Lyssa invites you on an exploration of the agile journey undertaken by Martin Kearns, a trailblazer who holds the distinction of being one of the first three coaches to earn the certified enterprise coaching designation. Martin is also a certified scrum trainer. In Martin's own words, she shares the emotional facets of his coaching journey and emphasizes the pivotal role of mindset in the agile realm. Martin explores the nuances between teaching and coaching, providing valuable insights into these distinct yet interconnected aspects of the agile landscape. Episode 5: Kathy Harman's Agile Coaching Journey In this episode, Lyssa takes you through the agile journey of Kathy Harman, business analyst and master agile coach. In Kathy's own words, she narrates her journey to achieving coaching competencies as a live coach. She considers the importance of recognizing and understanding agile ideals of coaching and of self-managed teams to fully embrace agile practices. Part II: Daily Practices for Agile Coaches Episode 1: Monday's Aphorism I relinquish my plan; I act in the moment to offer what they most need. Episode 2: Tuesday's Aphorism I am only partially right; I stay curious and see how others are right. Episode 3: Wednesday's Aphorism People act from good intention; I remain open to discovering it. Episode 4: Thursday's Aphorism Mistakes and messiness are necessary; we are all learning. Episode 5: Friday's Aphorism Excellence exists and is worth pursuing. Lyssa Adkins has taught Scrum to hundreds of students, coached many agile teams, and served as master coach to many apprentice coaches since 2004. Coaching coaches one-on-one and in small groups, she enjoys a front-row seat as remarkable agile coaches emerge and go on to entice the very best from the teams they coach. Prior to agile, Adkins had more than fifteen years of expertise leading project teams and groups of project managers in large and small consulting firms, commercial software companies, and the Fortune 500, yet nothing prepared her for the power of agile done simply and well. She teaches the "Coaching Agile Teams" training course, which allows agile coaches to learn, practice, and deepen the skills and mind-sets offered in the book. About Pearson Audio Learning Pearson publishes expert-led audio learning so you can dip into today's most important tech topics--wherever you are, wherever you go. Listen to industry leaders share first-hand experience, insights, and best practices using essential and emerging technologies.
Online resource; title from title details screen (O'Reilly, viewed January 17, 2024)
Keywords: Executive coaching; Teams in the workplace; Project management; Accompagnement de gestionnaires; Équipes de travail; Gestion de projet; Audiobooks; Livres audio